Blood-Brain Barrier Permeability Abnormalities in Vascular Cognitive Impairment - Taheri, Saeid (2011)
BACKGROUND AND PUROSE: Disruption of the blood-brain barrier (BBB) has been proposed to be important in vascular cognitive impairment (VCI). Increased cerebrospinal fluid (CSF) albumin and contrast-enhanced MRI provide supporting evidence, but quantification of the BBB permeability in patients with VCI is lacking. Therefore, we acquired dynamic contrast-enhanced MRI (DCEMRI) to quantify BBB permeability in VCI. METHOD: We studied 60 patients with suspected VCI. They had neurological and neuropsychological testing, permeability measurements with DCEMRI and lumbar puncture to measure albumin index (Q(alb)). Patients were separated clinically into subcortical ischemic vascular disease (SIVD), multiple and lacunar infarcts (MI/LAC), and leukoaraiosis (LA). Twenty volunteers were controls for the DCEMRI studies, and control CSF was obtained from 20 individuals undergoing spinal anesthesia for non-neurological problems. RESULTS: Thirty-six patients were classified as SIVD, 8 as MI/LAC and 9 as LA. The Q(alb) was significantly increased in the SIVD group compared to 20 controls. Permeabilities for the VCI patients measured by DCEMRI were significantly increased over controls (p<0.05). Patient age correlated with neither the BBB permeability nor Q(alb). Highest Q(alb) values were seen in SIVD group (p<0.05), and were significantly increased over MI/LAC. K(i) values were elevated over controls in SIVD, but were similar to MI/LAC. CONCLUSIONS: There was abnormal permeability in white matter in patients with SIVD as shown by DCEMRI and Q(alb). Future studies will be needed to determine the relationship of BBB damage and development of WMHs.